Microstructure and mechanical properties of AISI 439 ferritic stainless steel welds without filler metal - Salgado López, Juan Manuel; Preud homme, Marc; Lopez Monroy, Francisco; Ojeda Elizarráraz, Jose Luis; Toscano Giles, Arturo (Acta Universitaria, 2019)
In literature, it has been reported that a current intensity lower than 120 A leads to a microstructure without grain growth in the heat affected zone (HAZ) of ferritic stainless steel welds. Nevertheless, in technical literature there is little information about the reduction in mechanical properties of ferritic stainless steel welds without filler metal due to grain growth in the HAZ. In this work, thin plates of ferritic stainless 439 steel were welded using pulse current gas tungsten arc welding (P-GTAW) without filler metal. The microstructures in the HAZ were analyzed and the mechanical properties on the welded joint were found by tensile test. This was carried out by cutting samples for the tensile test from the weldments and then tested in a universal testing machine. The fracture surface were observed using scanning electron microscope.